Market Orientation, Product Innovation, and Competitive Advantage: Effects on Marketing Performance - Wulandari, Nurlaily; Sanusi, Ivan (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Economic competition is inevitable and increasingly intense, especially among micro, small, and medium enterprises (MSMEs). This can be seen from the growing number of MSMEs contributing to the dynamics of the global economy. In Indonesia, MSMEs face the challenge of adapting to global competition by optimizing internal and external resources. A major issue they encounter is the lack of strategic capability in achieving competitive advantage. This study aims to analyze the influence of market orientation, product innovation, and competitive advantage on marketing performance, with a case study of Keris MSMEs in Aeng Tong-tong Village, Saronggi District. A quantitative approach was used, with a census sampling method involving 107 respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that market orientation, product innovation, and competitive advantage each have a significant effect on marketing performance. Additionally, these three variables also influence marketing performance simultaneously. The findings highlight the importance of aligning market needs, continuous innovation, and maintaining unique competitive values to enhance MSME marketing effectiveness.